2018
DOI: 10.14393/obv2n2a2018-8
|View full text |Cite
|
Sign up to set email alerts
|

O pensar teórico e empírico em um curso de escrita acadêmica em inglês: por uma relação de agência do indivíduo com a língua

Abstract: A educação não tem privilegiado o pensamento teórico, apesar de ser possível proporcioná-lo no ensino escolar, segundo os pressupostos do ensino desenvolvimental. Neste artigo, analizo o desenvolvimento do pensamento teórico de uma aluna (LA) ao resolver um problema em um curso de escrita acadêmica em inglês. O curso foi criado com base no ensino desenvolvimental que objetivou trabalhar o conceito abstrato de língua (língua« contexto social) manifestado em gêneros textuais. Pela análise dos dados, LA mostra s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…In general, poor background is blamed for the weak writing skills displayed by students, and little action is taken to remedy the situation. General academic literacy courses described by Stella & Silva (2018) Ferreira (2018) and confirmed by the survey in the study. Although the intentions of the organisers of these workshops may be the best, these short sessions rarely go beyond superficial advice to potential authors and accomplish very little in terms of writing instruction.…”
Section: Academic Writing Instructionsupporting
confidence: 81%
“…In general, poor background is blamed for the weak writing skills displayed by students, and little action is taken to remedy the situation. General academic literacy courses described by Stella & Silva (2018) Ferreira (2018) and confirmed by the survey in the study. Although the intentions of the organisers of these workshops may be the best, these short sessions rarely go beyond superficial advice to potential authors and accomplish very little in terms of writing instruction.…”
Section: Academic Writing Instructionsupporting
confidence: 81%
“…Common pedagogical interventions in English for Research Publication Purposes (ERPP) may come in the form of workshops and short courses offered at universities and research institutions -as indicated by Ferreira (2018) and confirmed by the survey in the study. Although the intentions of the organisers of these workshops may be the best, these short sessions rarely go beyond superficial advice to potential authors and accomplish very little in terms of writing instruction.…”
Section: Academic Writing Instructionmentioning
confidence: 63%
“…Although an increase in the demand for more solid, genre-based courses on writing for publication in English such as the one described by Ferreira (2018) has been observed recently 9 , there are still few 9…”
Section: Academic Writing Instructionmentioning
confidence: 99%
See 2 more Smart Citations